Assessing on The Utilization of Emerging Technology Tools For Teaching Among Secondary School Teachers in Ilorin Metropolis - Aderonke Kofo Soetan; Amos Ochayi Onojah; Akorede Adetayo (IJER (Indonesian Journal of Educational Research), 2022)
Emerging technology is a term generally used to describe a new technology, but it may also refer to the continuing development of an existing technology; This project research was aimed at finding out assessing on the utilization of emerging technology tools for teaching among secondary school teachers Ilorin metropolis. The objectives of the study were to: (i.) Examine the available emerging technology tools. (ii.) Determine secondary school teacher level of utilization of emerging technology tools for teaching (iii.) and Determine the influence of utilization of emerging technology tools by teachers on students’ academic performance. A structured questionnaire tagged “Assessing on the utilization of emerging technology tools for teaching among secondary school teachers in ilorin metropolis, was utilized in the course of this research, thus a total of one hundred (100) questionnaires were administered by the researcher to teachers in randomly selected secondary schools in Ilorin metropolis. The analysis and interpretation of data gathered through the researcher-designed questionnaire was done using mean, percentage and frequency count. ANOVA was used for the hypothesis. The responses were analyzed based on research questions presented for the study using Statistical Package for Social Sciences (SPSS) at the significance level of 0.05. The research questions were analyzed with frequency count and percentage while the research hypotheses one was tested and analyzed using t-test. The findings of the study showed that; Majority of the respondents which constituted to about 54.2% of the whole sample were female; Majority of the respondents that participated in this study were those who had 10-20 years working experience .with a total of 57.7%; People with BED were majority in this study with a total of 43%; There was a significant relationship between gender and utilization of technology tools for teaching. Based on the findings from this study, the following recommendation were suggested; School management should endeavor to provide more technological tools in their schools to foster learning; Teachers should be aware of the innovations in the technology world and should know how to manipulate these tools in teaching and learning processes; and Utilize new digital apps and software (like Clickers, Socrative, Kahoot, Plickers and RecaP) that aid them to apply formative assessment in their classrooms. These technologies collect real-time formative assessment data that help teachers provide instant feedback